Promoting photocatalytic CO2 reduction with a molecular copper purpurin chromophore - Yuan, Huiqing; Cheng, Banggui; Lei, Jingxiang; Jiang, Long; Han, Zhiji (Nature communications, 2021)
CO 2 reduction through artificial photosynthesis represents a prominent strategy toward the conversion of solar energy into fuels or useful chemical feedstocks. In such configuration, designing highly efficient chromophores comprising earth-abundant elements is essential for both light harvesting and electron transfer. Herein, we report that a copper purpurin complex bearing an additional redox-active center in natural organic chromophores is capable to shift the reduction potential 540 mV more negative than its organic dye component. When this copper photosensitizer is employed with an iron porphyrin as the catalyst and 1,3-dimethyl-2-phenyl-2,3-dihydro-1 H -benzo[ d ]imidazole as the sacrificial reductant, the system achieves over 16100 turnover number of CO from CO 2 with a 95% selectivity (CO vs H 2 ) under visible-light irradiation, which is among the highest reported for a homogeneous noble metal-free system. This work may open up an effective approach for the rational design of highly efficient chromophores in artificial photosynthesis. Designing highly efficient chromophores comprising earth-abundant elements is essential for both light harvesting and electron transfer reactions. Here, authors prepare a copper purpurin complex that shows enhanced photocatalytic activity for CO 2 reduction to CO with a high selectivity.